Tilbage før syndefaldet? Karen Blixens ”Ringen” og et bud på en ikke helt uskyldsren kontrapunktisk litteraturpædagogik - Arndal, Lars S. (K&K - Kultur og Klasse, 2015)
Some voices in the recent field of literary theory argue that theory itself must be suspended. This is seen for instance in the case of Wendy Steiner, who characterizes the development of competing theories within the field of literature since the emergence of semiology as a ‘scientific parody’. This situation has led her to giving up ‘being a scientist’. The article argues against this retreat from theory. Rather than suspending theory, education in literature must use theories in a contrapuntal praxis of reading. This praxis is demonstrated in a reading of Karen Blixen’s short story, “The Ring”, which includes a discussion of Leif Søndergaard’s interpretations of the short story in K&K 73, 1993 . Even though Søndergaard uses a wide range of literary methods, it turns out that they all rely on a narratological structure in which the female protagonist, Lise, is transformed from innocent girl to a mature woman, who then turns her back on her newly wedded husband. Furthermore, it turns out that the readings in which Søndergaard engages rest on a symbolic reading of a few central places in the text. The article shows how Blixen’s text in itself both contradicts this narratological structure and the interpretation of symbols. On the narratological level there is not a before and after the Fall: Lise has already taken the step from girl to mature woman before the short story even begins. On the other hand, a literal reading of what at first seem to be metaphors and symbols shows that the short story itself dismantles the symbols which at first glance seem to be important. However, this insight is strongly dependent on Søndergaard’s thorough investigation of the text with the methods provided by different theories of literature. A contrapunctual reading would thus firstly follow the paths which seem to be laid out by the text, and secondly show how this interpretation of the text is in itself determined by the methodological approach.